PENGARUH GENDER, ETHICAL SENSITIVITY, LOCUS OF CONTROL DAN PEMAHAMAN KODE ETIK PROFESI AKUNTAN TERHADAP PERILAKU ETIS MAHASISWA AKUNTANSI UNIVERSITAS ISLAM MALANG - Mely Afriani; Noor Shodiq Askandar; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT Basically, prospective accountants want to be professional for their profession, therefore accountant students who are still pursuing academics have the power to introspect themselves based on ethical behavior. Because the crisis of knowledge morality of ethical valuesresults in a person acting outside the norm. So this research is to examine factors that can change accounting students to behave ethically. This analysis uses independent variables ‘gender, ethical sensitivity, locus of control and an understanding of the accounting code of ethics with the dependent variable of ethical behavior’. The population taken is accounting students of 2015 Islamic university. From the results of the 97 distributed direct questionnaires consisting of students and students using probability sampling methods and multiple linear regression testing. The results of this study indicate that gender, ethical sensitivity and understanding of the professional code of ethics of accountants positively influence student ethical behavior while locus of control is significantly negative towards ethical behavior.Keywords: Ethical behavior, gender, ethical sensitivity, locus of control and ethical codes of the accounting profession,